2001
DOI: 10.1021/jp012340s
|View full text |Cite
|
Sign up to set email alerts
|

Transient Negative Species in Supercritical Carbon Dioxide:  Electronic Spectra and Reactions of CO2 Anion Clusters

Abstract: Transient absorption spectra following ionization of supercritical CO2 have been investigated using the pulse radiolysis technique. Absorption spectra measured from 400 to 800 nm suggest that at least two transient species absorb. We have previously reported that one species is (CO2)2 +. In the near UV region, we observed a transient species of which the lifetime and reactivity are different from the dimer cation. We assign this species to a dimer anion, (CO2)2 -, or an anion−molecule complex, (CO2 -)(CO2) x .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
43
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 65 publications
4
43
1
Order By: Relevance
“…The differences between gas and condensed phase are not confined to N 2 O solutions. For e.g., we have demonstrated for CO 2 molecules that the CO À 2 anion is unstable in the gas phase while the CO À 2 anion is stable in water and CO 2 dimer anion is stable in supercritical CO 2 [14,15]. The reactivity of CO 2 and the CO À 2 anion in a high-density supercritical CO 2 is significantly different from that in gas phase [15].…”
Section: Introductionmentioning
confidence: 91%
“…The differences between gas and condensed phase are not confined to N 2 O solutions. For e.g., we have demonstrated for CO 2 molecules that the CO À 2 anion is unstable in the gas phase while the CO À 2 anion is stable in water and CO 2 dimer anion is stable in supercritical CO 2 [14,15]. The reactivity of CO 2 and the CO À 2 anion in a high-density supercritical CO 2 is significantly different from that in gas phase [15].…”
Section: Introductionmentioning
confidence: 91%
“…Supercritical CO 2 (scCO 2 ), a nontoxic, nonflammable, easily recyclable, and environmentally friendly solvent, appears to be a promising medium for charge-transfer reactions, and for reprocessing nuclear waste [18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Unlike polar water, ammonia, alcohols, and apolar or weakly polar organic solvents, a CO 2 molecule is bond polar but overall apolar and has a large negative gas phase vertical electron affinity (À 0:9 eV) [26,27], indicating that it can not directly bind an EE.…”
mentioning
confidence: 99%
“…Unlike polar water, ammonia, alcohols, and apolar or weakly polar organic solvents, a CO 2 molecule is bond polar but overall apolar and has a large negative gas phase vertical electron affinity (À 0:9 eV) [26,27], indicating that it can not directly bind an EE. However, bending vibrations can lead to a transient dipole for each CO 2 , and thus to its potential to bind an EE.…”
mentioning
confidence: 99%
“…While the electron affinity of CO 2 has been measured to be negative, equal to −0.6 eV in the gas phase, 24 Takahashi et al 25 have shown that a solvent with a dielectric constant between 1.5 and 2 is sufficient to stabilize the additional electron. CO 2 − is thus stable in an argon matrix that has a dielectric constant of 1.7, as it has been observed in several experimental studies in argon 21,26 and in neon.…”
Section: Introductionmentioning
confidence: 99%